“Short agonist stop” protocol, an ovarian stimulation for poor responders in in vitro fertilization (IVF): A pilot study - Mauries, Charlotte; Ranisavljevic, Noemie; Mollevi, Caroline; Brunet, Cecile; Hamamah, Samir; Brouillet, Sophie; Anahory, Tal (Frontiers in Endocrinology, 2022)
Introduction: Poor responder patients remain a challenge in assisted reproductive technologies. The “short agonist stop” (SAS) stimulation protocol uses a double stimulation (flare up effect with the gonadotropin-releasing hormone (GnRH) agonist (GnRH-a) then gonadotropins) associated with a less strenuous blockage (discontinuation of GnRH-a) to favor follicular recruitment in order to obtain a better ovarian response. This study aims to compare the number of oocytes obtained after a SAS stimulation protocol with those obtained after the previous stimulation protocol, in the same women, with poor ovarian response (POR) diagnosed according to the POSEIDON criteria. Design: This therapeutic observational retrospective cohort from 2018 to 2022, with a case-control evaluation compared with the same patients’ previous performance, included women with POR undergoing IVF with SAS stimulation protocol. The primary outcome was the number of total oocytes recovered and secondary outcomes were the numbers of mature oocytes, total embryos observed at day 2 and usable cleaved embryos and blastocysts (day 5/6). Results: 63 patients with SAS and previous cycles were included. In the SAS group, the mean number of oocytes was significantly higher: 7.3 vs 5.7, p=0.018 in comparison with the previous attempt. So was the number of mature oocytes (5.8 vs 4.1, p=0.032) and the total mean number of embryos obtained at day 2 (4.1 versus 2.7, p=0.016). The SAS stimulation generated 84 usable embryos: 57 cleaved embryos and 27 blastocysts. The mean number of usable embryos was similar in both groups (1.64 vs 1.31, respectively, p=0.178). In total, out of 63 patients, after the SAS protocol, and subsequent embryo transfers (fresh and frozen, n=54), 9 patients had ongoing pregnancies and no miscarriage occurred. The cumulative ongoing pregnancy rate (cOPR) after the SAS protocol was 14.3% (9/63) per oocyte pick-up and 16.7% (9/54) per transfer. Conclusion: SAS stimulation is a short and original protocol strengthening the therapeutic arsenal of poor responders, that may offer promising results for those patients with low prognosis and previous failed IVF. Results must be confirmed with a randomized controlled trial.